2009
DOI: 10.1007/s00442-009-1483-x
|View full text |Cite
|
Sign up to set email alerts
|

Family movements before independence influence natal dispersal in a territorial songbird

Abstract: Dispersal behaviour in territorial species is typically assumed to be independent of parental behaviour except for the possible role of parental eviction from the natal territory. Great tits defend exclusive territories at the onset of breeding but after fledging undertake substantial excursions with dependent offspring, sometimes covering distances equivalent to ten or more breeding territories and even moving across open spaces into neighbouring woodlots. We show that postfledging family movements are signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Yet, in both species and in house sparrows near the city of Ghent, levels of relatedness were consistently higher in urban populations (Riegert et al, 2010;MacDougall-Shackleton et al, 2011;Vangestel, 2011). Although such results could indicate subtle differences in connectivity between both areas, highly synchronized postnatal dispersal directions of siblings through parental control (Matthysen et al, 2010) or area-dependent levels of complete nest predation (MacDougall-Shackleton et al, 2011) might increase genetic similarity between individuals as well. In contrast, urban great tit (Parus major) populations showed higher genetic variation compared with forest populations, possibly indicating higher gene flow from urban parks to forests than vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, in both species and in house sparrows near the city of Ghent, levels of relatedness were consistently higher in urban populations (Riegert et al, 2010;MacDougall-Shackleton et al, 2011;Vangestel, 2011). Although such results could indicate subtle differences in connectivity between both areas, highly synchronized postnatal dispersal directions of siblings through parental control (Matthysen et al, 2010) or area-dependent levels of complete nest predation (MacDougall-Shackleton et al, 2011) might increase genetic similarity between individuals as well. In contrast, urban great tit (Parus major) populations showed higher genetic variation compared with forest populations, possibly indicating higher gene flow from urban parks to forests than vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Social interactions between individuals, including behaviors such as territoriality (Stamps 1994), also influence space use within avian populations (Gauthreaux 1978, Wunderle 1991, Griesser et al 2007. Kinship may also influence space use, for example, during cooperative breeding (Hatchwell 2009), during the fledgling-dependence period (Matthysen et al 2010), and during natal dispersal (Matthysen et al 2005). Resource specialization due to morphological differences (Phillips et al 2004, Catry et al 2005 or different nutritional requirements (Safi et al 2007) also sometimes relate to differences in intraspecific space use.…”
Section: Differences In Space Use By Common Ravens In Relation To Sexmentioning
confidence: 98%
“…KINSHIP AND SPACE SHARING DURING JUVENILES' DISPERSAL Movements of parents and dependent offspring beyond the parents' normal range occur in several species (Nack and Anderson 2006, Matthysen et al 2010, van Overveld et al 2011). Our observations add to previous studies (Stiehl 1985, Webb et al 2009) of the raven that reported broodmates and parents associating during initial movements outside the natal territory.…”
Section: Site Fidelitymentioning
confidence: 99%
“…The dispersal rule of favoring intermediate distances could come about if individuals first move away from the natal site and then have a limited home range. In some cases, this move away from the natal site or part of it may come about before independence, which then leads to correlations in dispersal distances for siblings (Massot et al 1994;Matthysen et al 2010). Thus, although the dispersal rules used were formulated in terms of the resulting pattern, there are plausible mechanisms underlying them.…”
Section: Discussionmentioning
confidence: 99%